波长可变干涉滤波器及制造方法、光学模块以及电子设备 (2018)
本发明提供种波长可变干涉滤波器及制造方法、光学模块及电子设备。波长可变干涉滤波器（5）具备：变更固定反射膜（54）及可动反射膜（55）之间的间隙尺寸的静电致动器（56）；与静电致动器（56）连接的固定引出电极（563）及可动引出电极（564B）；及具备顶面部（531）和侧壁部（532）的第三基板（53），接合侧壁部（532）的端面及第基板（51），由顶面部（531）、侧壁部（532）以及第基板（51）围成的空间（D1）被气密密封，在空间（D1）中，配置有第二基板（52）及静电致动器（56），固定引出电极（563）及可动引出电极（564B）设置于第基板（51），跨空间（D1）的内外而延伸。 A wavelength tunable interference filter includes an electrostatic actuator that changes the dimension of a gap between a fixed reflection film and a movable reflection film, a fixed drawn electrode and a movable drawn electrode that are connected to the electrostatic actuator, and a third substrate having a top surface portion and a sidewall portion. An end surface of the sidewall portion is bonded to a first substrate so that a space surrounded by the top surface portion, the sidewall portion, and the first substrate is hermetically sealed. A second substrate and the electrostatic actuator are disposed in the space, and the fixed drawn electrode and the movable drawn electrode are disposed on the first substrate an